2020
DOI: 10.1017/jfm.2020.472
|View full text |Cite
|
Sign up to set email alerts
|

Electrically driven toroidal Moffatt vortices: experimental observations

Abstract: Abstract

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
19
0
1

Year Published

2021
2021
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(21 citation statements)
references
References 23 publications
(57 reference statements)
1
19
0
1
Order By: Relevance
“…This result is qualitatively consistent with the experimental observation of Perri et al. (2020), who also reported a transient flow experiencing bifurcation. Furthermore, we found that increasing the charge diffusion effect can increase the size of vortices in this EHD flow.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…This result is qualitatively consistent with the experimental observation of Perri et al. (2020), who also reported a transient flow experiencing bifurcation. Furthermore, we found that increasing the charge diffusion effect can increase the size of vortices in this EHD flow.…”
Section: Discussionsupporting
confidence: 93%
“…In Perri et al. (2020), the authors observed transient EHD flows, suggestive of flow bifurcation to another state. In our numerical simulations, we can also observe an unsteady flow when increasing in the blade–plate EHD flow.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…聚苯乙烯微球 [20] 。Chrikov 等对另一种维恩-昂萨格效 应泵流动以及针-板结构电荷注入-传导机制电对流进 行了 PIV 流场测量,直径 1-10 微米的硼硅酸盐空心 球作为示踪粒子 [82,83] 。法国普瓦捷大学 Louste 等人较 为系统地开展了介电液体电流动 PIV 测量工作,讨 论了示踪粒子材料和浓度对测量结果的影响 [84,85] 。他 们早期研究由电荷注入引起的流动 [86] ,近年来开始 关注电导机制引起的流动 [87] 以及电荷注入-传导的过 渡过程 [43] 。图 14 展示了一个封闭墙体内,9 对非对称 平嵌电极(一对电极宽度分别为 1.3mm 和 3.8mm) [88,89] 。电 导泵 PIV 测量工作还较少,且都是在封闭腔体内进 行,没有外部流动。另外,PIV 测量结果显示简单的 平板嵌入电极电导泵在低电压下的流场结构也很混 乱 [86,87] ,说明电导泵内复杂流动特征和机理还有待深 入研究。其他更复杂电极结构电导泵 PIV 测量还未有 开展。 measured by PIV in a confined cavity [87] 微尺度电导泵(电极间距为几十微米到几百微…”
Section: 示了电极结构设计对电导泵性能有重要影响。unclassified